The soul of America : the battle for our better angels - Meacham, Jon (Random House, 2018)
"The current climate of partisan fury is not new, and in The Soul of America, Meacham shows us how what Lincoln called the "better angels of our nature" have won the day. Painting surprising portraits of Presidents, including Abraham Lincoln, Theodore Roosevelt, Ulysses S. Grant, Woodrow Wilson, Franklin D. Roosevelt, Harry S. Truman, Dwight Eisenhower, Lyndon B. Johnson, and others, and illuminating the courage of such influential citizen activists as Martin Luther King, Jr., early suffragettes Alice Paul and Carrie Chapman Catt, civil rights pioneers Rosa Parks and John Lewis, First Lady Eleanor Roosevelt, and Army-McCarthy hearings lawyer Joseph N. Welch, Meacham brings vividly to life turning points in American history. He writes about the Civil War, Reconstruction, and the birth of the "Lost Cause"; the backlash against immigrants in the First World War and the resurgence of the Klu Klux Klan in the 1920s; the fight for women's rights; the demagoguery of Huey Long and Father Coughlin and the isolationist work of "America First" in the years before World War II; the Communist witch hunts led by Senator Joseph McCarthy; and Lyndon Johnson's crusade to finish the fight against Jim Crow. In each of these dramatic, crucial turning points, the battle to lead the country to look forward rather than back, to assert hope over fear, was joined, even as it is today. While the American story has not always or even often been heroic, and the outcome of that battle has never been certain, in this inspiring book, Meacham writes, "The good news is that we have come through darkness before," as time and again, Lincoln's better angels have found a way to prevail"--